﻿Ideologia da casa própria... sem casa própria: o Programa de Arrendamento Residencial na cidade de João Pessoa-PB - Bonates, Mariana Fialho (2007)
﻿Brazilian Housing policy has always promoted homeownership. In 1999, a new form of housing promotion was set up in the country with the PAR (Programa de Arrendamento Residencial, or residential rental programme). This is a sort of leasing, in which a right to buy is granted at the end of contract. Again, with this, the final objective is homeownership. This dissertation aims at further understanding the role of PAR in the wake of the country s housing policies of the post-BNH period, analysing the case of João Pessoa, capital city of Paraíba state. By focusing in the city, it has been possible to analyse also the impact of the programme in the dynamics of the city s urban development. Accordingly, the analysis of PAR seeks to understand the programme s operational aspects as well as its location, urban and architectural aspects. The operational aspects refer to how the programme is operated, considering the differences to the other housing programmes in the country. The urban and architectural aspects refer to location, typology and construction characteristics of housing estates produced under the scheme. This study gives a general view of the country s recent housing policy and programmes and the specific characteristics of PAR, observing also its impacts in the city development